Effect of curcumin on glioblastoma cells. Issue 7 (26th December 2018) - Hesari, AmiReza; Rezaei, Marzieh; Rezaei, Maryam; Dashtiahangar, Maryam; Fathi, Mozhgan; Rad, Jeyran Ganji; Momeni, Fatemeh; Avan, Amir; Ghasemi, Faezeh
Abstract: Curcumin is a polyphenolic compound derived from Curcumin longa L. There are growing bodies of evidence revealing the antitumor effect of curcumin in different tumors; although the molecular mechanism behind this inhibition in glioblastoma multiform (GBM) still remains unclear. Here we investigated the antitumor activity of nano micelles curcumin compared with erlotinib in U‐373 cells in monolayer cell cultures and spheroids models. Furthermore, we characterized affecting cell cycle perturbation, as well as apoptosis induction in GBM cells. The antiproliferative activity of nano micelles curcumin and erlotinib were assessed in monolayer and spheroid models. The influence of the cell cycle and expression levels of nuclear factor κB (NF‐κB) and Wnt/β‐catenin pathway was checked. Nano micelles curcumin suppressed cell growth in U‐373 cells via modulation of Wnt and NF‐κB pathways. Moreover, cells developed an early G2/M cell cycle arrest followed by sub‐G1 apoptosis and apoptotic bodies formation posttreatment with nano micelles curcumin and erlotinib. In the core signaling pathways of GBM, nano micelles curcumin either significantly influences the NF‐κB pathway by decreasing p‐65 expression or significantly inhibits the Wnt/β‐catenin pathway by declining cyclin D1 expression. In conclusion, we have shown that nano micelles curcumin effectively prevent proliferation, and invasion of GBM cells through perturbation of Wnt/β‐catenin and NF‐κB pathways, suggesting further investigations on the therapeutic application of this novel anticancer drug in in vivo models.